Resort Management Practices and Tourism Impacts of an Island Resort in Negros Occidental - A. Villarias, Rose Ann (Technium Sustainability, 2021)
This descriptive study assessed the extent of the resort’s management practices based on sustainable development principles in terms of corporate governance, decision-making, environmental safety and risk management, stakeholder’s engagement, culture and human rights, community development, continuous improvement, biodiversity and land use planning, and waste management. Likewise, it also examined the extent of island resort’s tourism impacts in terms of economic, social, and environmental dimensions. The overall findings revealed that the extent of the resort management practices in all areas was "moderate extent," which means the resort management practices are sometimes practiced. In terms of the extent of tourism impacts of resort management practices, findings revealed that it is also to a "moderate extent," which means the resort management practices have an average impact. It indicates that the island resort incorporates good management practices by incorporating sustainable initiatives that can positively influence its business operations and external environment. However, the study results can also validate that there is a need for improvement in the area of community development. Moreover, the resort’s environmental management must be prevalent and considered in the overall business operation to contribute to environmental footprints.